Wind Power Plant Site Selection Using Fuzzy AHP and Weighted Fuzzy Overlay - Mehmet Fatih Döker; Esra Özdoruk; Cem Kırlangıçoğlu; Masoud Minaei (Wind Energy)
ABSTRACT The availability of energy is a fundamental prerequisite for technological and economic advancement. Although the majority of contemporary energy requirements are fulfilled by fossil fuels, the transition towards sustainable and efficient energy sources is gathering pace. Wind energy, a renewable energy source, has the potential to significantly contribute to energy independence. The objective of this study is to ascertain the most appropriate locations for the construction of wind power plants in Sakarya Province, thereby facilitating energy independence through an enhanced energy supply. The study identified economic, environmental, and physical criteria and excluded areas and conducted analyses using multicriteria decision‐making methods. The relative importance weights of the criteria were calculated using the fuzzy analytic hierarchy process, and the results obtained were realistic. This was achieved using the weighted fuzzy modeling method. The analysis, which focused on Sakarya Province, revealed that the Kaynarca, Hendek, Söğütlü, Adapazarı, Akyazı, Taraklı, Geyve, and Pamukova districts possess considerable potential for wind energy. The results demonstrate that renewable sources currently account for only 21% of Sakarya's electricity demand. However, the installation of 315 wind turbines has the potential to meet this demand entirely through renewable sources. The estimated cost of these turbines is approximately $1.26 billion, with a required area of 693 ha. The identification of a total of 7541 ha of suitable land indicates that there is sufficient land available for investment. It is recommended that future studies analyze investment and maintenance costs and electricity demand based on population projections.